2000
DOI: 10.1038/sj.ejcn.1601042
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variability in dietary intake in two distinct regions of rural India: implications for nutrition study design and interpretation

Abstract: Objective: Limited inter-person variability in nutrient intake hampers epidemiologic studies of diet ± disease relationships. Despite conjecture about non-traditional study bases providing large inter-person differences, virtually nothing is known about variations in nutrient intake outside of Europe and North America. The current study was conducted in India to determine sources of variability in the intakes of nutrients thought to be of public health importance. Design: Adult subjects in Gujarat (North India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
39
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 35 publications
8
39
0
Order By: Relevance
“…The interpersonal variance found by the present study was the greatest source of nutrient intake variance, resulting in a VR of less than 1 and corroborating the findings of Laningan et al 1 in children and Herbert et al 24 in adults. The lack of variation in habitual dietary intake can be attributed to the low purchasing power and low education levels of the study population.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The interpersonal variance found by the present study was the greatest source of nutrient intake variance, resulting in a VR of less than 1 and corroborating the findings of Laningan et al 1 in children and Herbert et al 24 in adults. The lack of variation in habitual dietary intake can be attributed to the low purchasing power and low education levels of the study population.…”
Section: Discussionsupporting
confidence: 80%
“…Studies on food intake and dietary patterns done in other regions of Brazil found a VR greater than 1, stemming from higher intrapersonal variance 13,14 . This demonstrates that the daily food intake of an individual is a random event, even though a particular group displays a stable food intake pattern 24 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence suggesting that the intake of total protein does not change by season (Hackett et al, 1985;Krauchi and Wirz-Justice, 1988;Hebert et al, 2000;Cai et al, 2004), as well as contradictory evidence of increased protein intake during the autumn and winter (Doyle et al, 1999). A separate study reported that the intake of protein showed suggestive, although not significant, seasonal changes (De Castro, 1991).…”
Section: Discussionmentioning
confidence: 94%
“…Others have suggested that three 24 h dietary recalls were best for estimating energy intake in normalweight women (9) . The number of days that dietary intake should be collected can be determined by estimating within-subject variance, which is the day-to-day variation in each individual's nutrient intake, and between-subject variance, which is the extent that individuals' nutrient intake varies from one another (10)(11)(12)(13)(14)(15)(16) . Several factors such as sex, day of the week, season, culture and environment influence nutrient variation (17)(18)(19) .…”
mentioning
confidence: 99%